Sport values and sustainability? - Tess Kate Schweizer; Nicolas Margas (Current Issues in Sport Science)
Introduction United Nations call for all nations to act together towards the Sustainable Development Goals (SDGs) and recalls that this collective transformation requires the development of shared values into citizens that are in line with SDGs. Sport is particularly highlighted in this perspective as it is supposed to intrinsically convey values associated to sustainability that would be internalized by practitioners. To go beyond this ideology, this study aims to review empirical findings establishing the values intrinsically salient in sport, their internalization or not by practitioners and the processes explaining this internalization.